Investigation of Possibility for Reducing AISI 303 Stainless Steel Pitting Corrosion by Microalloying with Boron or Zirconium - Bikić, Farzet; Mujagić, Derviš (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
AISI303 has the highest machinability comparing with all other austenitic stainless steel grades. The good machinability is a result of sulphur presence in the steel composition. Sulphur improves machinability but at the same time causes a decrease in the corrosion resistance.The aim of the research was to examine the possibility of reducing the effect of sulfur content on the corrosion behavior of AISI 303 by microalloying with boron or zirconium. The intention is to keep high machinability of this steel grade but make it corrosion resistant. The results show that after microalloying with boron or zirconium the intensity of pitting corrosion of AISI 303 stainless steel can be significantly reduced. The results show that the effect of reducing the intensity of pitting corrosion of AISI 303 stainless steel microalloyed with boron or zirconium is higher at lower concentrations of chlorides. This is confirmed trough comparing the intensity of pitting corrosion of the 303 stainless steel samples microalloyed with boron or zirconium with the samples of 304 stainless steel. The intensity of pitting corrosion 303 stainless steel microalloyed with boron or zirconium is closer to the intensity of pitting corrosion of 304 stainless steel in 1.5% NaCl solution than in a 3% NaCl solution. Results also clearly indicate that the increase of NaCl concentration leads to an increase of pitting corrosion in all tested samples.